1997
DOI: 10.1089/hum.1997.8.18-2261
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vectors for Gene Therapy of Cystic Fibrosis

Abstract: A replication-defective vector based on human immunodeficiency virus (HIV) was evaluated for gene transfer directed to the lung. The tropism of this vector has been expanded through the incorporation of the vesticular stomatitis virus G protein into its envelope. The HIV vector effectively transduced nondividing airway epithelial cells in vitro whereas a murine-based retroviral vector did not. Experiments in a human bronchial xenograft model demonstrated high-level gene transduction with a cystic fibrosis tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 21 publications
3
80
0
3
Order By: Relevance
“…Although C-type retroviruses have been used previously, the therapeutic potential of lentiviral vectors in the context of cancer gene therapy is an area which has so far been largely untested. [27][28][29] We investigated the optimal strategies for packaging the GALV FMG cDNA into both C-type and lentiviral vectors. Expression of GALV FMG will rapidly fuse human cell lines so that stable human packaging cell lines cannot be generated.…”
Section: Discussionmentioning
confidence: 99%
“…Although C-type retroviruses have been used previously, the therapeutic potential of lentiviral vectors in the context of cancer gene therapy is an area which has so far been largely untested. [27][28][29] We investigated the optimal strategies for packaging the GALV FMG cDNA into both C-type and lentiviral vectors. Expression of GALV FMG will rapidly fuse human cell lines so that stable human packaging cell lines cannot be generated.…”
Section: Discussionmentioning
confidence: 99%
“…In the only published study to date, HIV vectors pseudotyped with the vesicular stomatitis virus (VSV) glycoprotein (G) efficiently transduced undifferentiated airway epithelia, while failing to transduce the well differentiated pseudostratified columnar epithelium of mature human bronchial xenografts. 18 Given the potential advantages of HIV vectors, we explored the utility of this vector system in airway epithelia. After establishing whether HIV vectors could transduce non-dividing airway cells, we examined the ability of these vectors to transduce polarized epithelia in vitro via application of vector to the apical versus the basolateral surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…59 A first-generation VSV-G-pseudotyped HIV-1-derived vector was able to transduce wild-type CFTR into poorly differentiated human bronchial xenografts and its expression normalized both the chloride transport defect and reverted the bacterial killing activity. 39 Primary organotypic cultures of human trachea from patients with CF transduced with a VSV-G-pseudotyped FIVderived vector demonstrated Cl À secretion in response to cAMP agonists in a fashion similar to normal airway epithelia. 44 The correction of Cl À secretory response remained stable for 6 months.…”
Section: Correction Of the Cf Defectmentioning
confidence: 98%
“…11 Preliminary studies on the efficiency of HIV-1-derived vectors in transducing the respiratory epithelium of airway xenografts have shown that a proliferating and differentiating epithelium, but not a truly differentiated one, is susceptible to transduction. 39 Recent studies have confirmed that HIV-1-derived vectors could not transduce a fully differentiated airway epithelium unless it was injured. An HIV-1-derived vector transduced polarized tracheal epithelial cells from the apical surface only in the presence of the calcium chelator ethyleneglycol-tetraacetic acid (EGTA) and, however, at a much lower overall efficiency than was observed for polarized alveolar epithelial cells.…”
Section: Gene Transfer With Preconditioningmentioning
confidence: 99%